Agronomic Bio-fortification for ensuring Zn nutrition - Saha, Bholanath; Basak, Nirmalendu; Saha, Sushanta; Hazra, G. C.; Mandal, Biswapati (Indian Farming, 2015)
Plant nutrition-based research activities are indispensable in meeting food security needs. The fact that at least 60% of the presently cultivated soils globally are deficient in Zn, makes plant nutrition-based research a major promising research area needed to meet the demand for massive increases in food production required for the growing world population. One of the high priority objectives of plant-nutrition research will be ensuring a long-term sustainable nutrient management system for crop production, and developing more efficient mineral nutrient uptake by crop plants and improving intra- and intercellular use of nutrients without detrimentally affecting the environment. More research activities are, therefore, needed aiming at improving the bioavailable levels of Zn in cereal grains.